Psychometric evaluation of the Signs of Depression Scale with a revised scoring mechanism in stroke patients with communicative impairment - van Dijk, Mariska J; de Man-van Ginkel, Janneke M.; Hafsteinsdóttir, Thóra B; Schuurmans, Marieke J. (SAGE Publications Ltd, 2017)
Objectives: To investigate (1) the diagnostic value of the Signs of Depression Scale (SODS) in a Likert scale format and (2) whether the Likert scale improves the diagnostic value compared with the original dichotomous scale. Design: Cross-sectional multicentre study. Setting: One general and one university hospital in the Netherlands. Subjects: A total of 116 consecutive hospitalized stroke patients, of whom 53 were patients with communicative impairment. Main measures: Depression was diagnosed with the Composite International Diagnostic Interview (CIDI) administered to the patients’ relatives. The Barthel Index (BI) was used as an external validator. Results: The correlation between the CIDI and the SODS-Likert or the SODS was small (rb = 0.18), and the correlation between the Barthel Index and the SODS-Likert (rs = −0.30) or the SODS (rs = −0.33) was moderate. For both instruments, the discriminatory power for diagnosing depression when compared with the CIDI was best at a cut-off score of ⩾2. The internal consistency of the SODS-Likert was acceptable (α = 0.69) and slightly higher than that of the SODS (α = 0.57). The inter-rater reliability of the SODS-Likert and the SODS was acceptable (intraclass correlation coefficient (ICC) 0.66 and ICC 0.80, respectively). The clinical utility was rated good. Conclusion: The diagnostic value of the SODS did not improve using a Likert scale format. However, the diagnostic value of the original dichotomous SODS is reasonable for the initial mood assessment of stroke patients with communicative impairment.
Keywords: Screening; communication disorder; depression; psychometrics; stroke; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Journal Article